Removal of Ca2+ and Mg2+ from oilfield wastewater using reusable PEG/Fe3O4/GO-NH2 nanoadsorbents and its efficiency for oil recovery. Issue 1 (February 2021) - He, Lei; Yang, Lutao; Zhang, Luxia; Wang, Zhe; Cheng, Hongjie; Wang, Xiaoguang; Lv, Jianrong; Zhang, Jun; Mo, Hong; Shen, Jian
Graphical abstract: Highlights: The PEG/Fe3 O4 /GO-NH2 nanoadsorbent removed Ca 2+ and Mg 2+ from oilfield wastewater by 61–70 %. The nanoadsorbent had relatively high reuse rates of 69–80 % at the fifth recycling run. The oil recovery significantly increased by 11.8 % when the treated oilfield wastewater was reinjected. Abstract: The high salinity of oilfield-produced water caused by the presence of metal ions, such as Ca 2+ and Mg 2+, has a significantly adverse effect on oil recovery. It is crucial to remove these metal ions efficiently before the oilfield wastewater is reinjected down into the oil wells. To address this issue, we prepared a PEG/Fe3 O4 /GO-NH2 nanoadsorbent by aminating GO, incorporating magnetic Fe3 O4 nanoparticles and coating with PEG (PEG = poly(ethylene glycol); GO-NH2 = aminated graphene oxide). We investigated the removal ratios of the nanoadsorbent for Ca 2+ and Mg 2+ . The respective removal ratios for Ca 2+ and Mg 2+ reached 69.8 % and 61.1 % at 10 min, indicating that the nanoadsorbent was capable of efficiently removing Ca 2+ and Mg 2+ . We also evaluated the reusability of the nanoadsorbent by recycling and reusing it 5 times. At the fifth recycling run, the nanoadsorbent retained relatively high reuse rates (79.1 % for Ca 2+, 69.5 % for Mg 2+ ) and removal ratios (69.5 % for Ca 2+, 64.3 % for Mg 2+ ), suggesting that the nanoadsorbent possessed relatively high reusability. Oilfield wastewater treated with the nanoadsorbent was employed for oil recovery in core displacement experiments. The oil recovery efficiency significantly increased by 11.8 % compared with untreated oilfield wastewater. Therefore, the PEG/Fe3 O4 /GO-NH2 nanoadsorbent exhibits considerable potential for the treatment of oilfield wastewater to enhance oil recovery.